Developing safety and health assessment model as benchmark strategy to evaluate and measure the performance of contractor in JKR construction project - Shaiful Azman, Taha (2018)
Safety and Health Performance evaluation of construction projects have long been an issue due to the complexity of each project. There are no standard criteria that can be used as a benchmark to evaluate the safety performance of a construction company for a particular construction project. For construction projects under Jabatan Kerja Raya (JKR) valuing over RM20 million, two mandatory documents for submission are Safety and Health Plan before start of the project and monthly Safety and Health Report throughout the execution of the project. Theoretically, using these two documents as baselines, a standard benchmarking tool can be formulated to apply for future projects. A theoretical framework was developed from literature review to cover all important variables in crafting a Safety and Health Plan (and subsequently, the monthly SH Report). These variables were then formed into a survey in which 193 respondents consisting of personnel in safety and health field participated in order to determine their viability. Both the variables and results of the survey were then reviewed by a panel of experts to be analysed and refined. Based on their input, a benchmarking tool was formed. It was then applied to three randomly selected projects of various completion tages to evaluate its effectiveness in determining the performance of safety and health aspect in terms of their SH Plan. The same three projects are also evaluated using existing benchmark tool and the scores compared. The study concluded that the formulated benchmarking tool and its selected variables were consistent in determining the level of safety and health performance of the selected projects and that further refinement can be made in terms of its application on-site. It is also noted that all the projects evaluated had unacceptable level of safety performance regardless of the initial scoring received for SH Plan formulation. It is suggested that continuous monitoring and adjustment be made so that the benchmark variable can be further improved. In this regard, an online system can be developed to enable seamless integration of on-site assessment and off-site analysis of the generated results, enabling sharing and discussion among safety and health peers.